2020
DOI: 10.1039/d0ta04005c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for overcharging of carbon electrodes in lithium-ion/sodium-ion batteries analysed by operando solid-state NMR

Abstract: An in-depth investigation of the overlithiation/oversodiation and subsequent delithiation/desodiation of graphite and hard carbon electrodes in the first cycle was conducted using operando7Li/23Na solid-state NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 36 publications
2
61
1
Order By: Relevance
“…This temporary decrease in cell potential is associated with overcoming the overpotential for the nucleation of lithium metal on a substrates surface and is therefore assigned to the start of lithium metal plating. 23 The delithiation of the HCmicro-electrode exhibits a very long plateau region close to The two plateaus formed in delithiation of the carbons indicate the existence of two different delithiation mechanisms occurring in both carbons to different extent. The plateau up to 20 mV can be attributed to the stripping of metallic lithium from a 3D structured conducting material due to the small hysteresis between plating and stripping in the case of low current densities (0.05 mA cm -2 ).…”
Section: Hcmicromentioning
confidence: 90%
See 3 more Smart Citations
“…This temporary decrease in cell potential is associated with overcoming the overpotential for the nucleation of lithium metal on a substrates surface and is therefore assigned to the start of lithium metal plating. 23 The delithiation of the HCmicro-electrode exhibits a very long plateau region close to The two plateaus formed in delithiation of the carbons indicate the existence of two different delithiation mechanisms occurring in both carbons to different extent. The plateau up to 20 mV can be attributed to the stripping of metallic lithium from a 3D structured conducting material due to the small hysteresis between plating and stripping in the case of low current densities (0.05 mA cm -2 ).…”
Section: Hcmicromentioning
confidence: 90%
“…There are two possible lithium species known from literature forming at potentials near and slightly below 0 Vlithium clusters and lithium metal. 23,31 For the interpretation of the ConVol measurements, it is important to state that the minimum potential of the cell in constant voltage step was at -0.5 mV slightly below the intended 0 V due to the precision of the measurement device. However, this is at least one order of magnitude smaller than the overpotential for lithium metal plating observed in CC experiments e.g.…”
Section: Hcmicromentioning
confidence: 99%
See 2 more Smart Citations
“…However, from magnified charge-discharge curves in Figure 4 d, we confirmed that the sodiation potential plateau is located around 0.05 V vs. Na and lower, which is higher than that of the post-heated activated carbon at 2100 8C in a Na cell [5a] and sucrose-derived low postHTT hard carbon in a Li cell. [3d] The 23 Na MAS NMR signal at the lower-frequency shift of 1030 ppm for sodiated HC600-1500(F50:50) also implies more ionic state of sodium atoms compared to those reported for the sucrose-derived hard carbon at the postHTT of 2000 8C (1114 ppm). [10c] Therefore, the potential risk of [25] Angewandte Chemie Zuschriften metal plating for HC600-1500(F50:50) is lower than high postHTT hard carbon as well as high-capacity low-postHTT hard carbon in a Li cell.…”
Section: Angewandte Chemiementioning
confidence: 95%